Fatigue of crystallizable rubber: Generation of a Haigh diagram over a wide range of positive load ratios. (September 2021) - Champy, C.; Le Saux, V.; Marco, Y.; Glanowski, T.; Charrier, P.; Hervouet, W.
Highlights: We have generated an extensive Haigh diagram on a rubber-like material over a wide range of load ratio. A preliminary study is carried out to define an initiation criterion that remains valid for all the testing conditions. The Haigh diagram presents a bell shape with an improvement of the fatigue properties for positive load ratio up to R_d = 0.35. This shape is related to strain induced crystallization. Abstract: A Haigh diagram is built for a carbon black filled rubber blend that exhibits Strain Induced Crystallization (SIC) for a wide range of positive displacement ratios. A strategy for the initiation detection, which becomes difficult for high displacement ratios, is proposed and validated thanks to regular visual follow-up. Some experimental cautions are taken to avoid any temperature and strain rate effects on the results, more specifically on the strain induced crystallization phenomenon. It is found that a reinforcement related to strain induced crystallization is present for load ratios (up to displacement load ratio of 0.35). For higher load ratios, the reinforcement effect reduces leading to a Haigh diagram that looks like a bell, as already shown by Cadwell et al. (S. Cadwell, R. Merrill, C. Sloman, F. Yost, Dynamic fatigue life of rubber, Industrial and Engineering Chemistry 12 (1940) 19–23).